Exploring the Suitability of Six Sigma in M ajor Swedish Construction Companies - Sjöqvist, Olof; VRBANC, MICHAEL (My University, 2016)
In the Swedish construction industry there is a lack of systematic quality development. In contrast, the manufacturing industry has continuously been working with quality development with the help of different methodologies. One such methodology is Six Sigma where a team is trained to use DMAIC and different graphical and statistical tools in quality improvement projects to reduce the DPMO. This report examines if major Swedish construction companies could benefit from the use of Six Sigma and studies what would be required in order to implement the methodology. Also, some of the tools within Six Sigma are examined and their suitability to construction is discussed. The study was conducted partly by researching literature and partly by interviewing people who work with quality in different ways, mainly in construction but also with a Six Sigma expert at Volvo Cars. The results of the study indicate that the way in which construction companies report their variations is insufficient and that there is a lack of measurement databases which hinders the use of Six Sigma. Also, the results point towards a low competition on the Swedish construction market leading to low pressure on the construction companies to develop their quality. The study shows a few examples of beneficial Six Sigma implementation in construction and by Bechtel Corporation. Finally, the results indicate that Volvo Cars has gotten further ahead than the construction industry when it comes to quality awareness and controlling their processes because of factors such as higher pressure from outside stakeholders and harder market competition. In conclusion, the construction industry should include quality awareness in their company cultures and at least start to move from zero defects in the end product to zero defects in the project process which would result in the same thing but with less expenses for the company. The next step should be to use softparameter based tools and to start measuring and documenting defects and variations systematically to enable systematic quality development. Also, it should be possible to standardise to a much higher degree than today in order to further decrease variation. If the aforementioned actions were taken it would surely be possible to use Six Sigma to further optimise the processes within construction and continuously develop the quality.
Keywords: Samhällsbyggnadsteknik; Civil Engineering